The Applicable Law to the International Contract between Particulars in the Project of Title Preliminary of the Peruvian Civil Code - Revoredo de DeBakey, Delia (1978)
The purpose of the Reform Commission of the Civil Code was to regulate the law of the international contract between individuals. In the same Article XLIII of the Draft Preliminary Title that authorized the parties to submit the contract to a foreign law and foreign to it that no longer expressly requires that an objective link between the contractual relationship and the country whose law requires the parts. In this sense, it departs from the criterion embodied in the legislative history and the preferred systems in Comparative Law, with respect to the determination of the law applicable to the international contract between individuals. Likewise, the importance of the content of art. XLIII in which the contracting parties would be empowered to indicate the competent law, would be incompatible with the prohibition of "circumventing the competent Peruvian law" contained in Article XVI of the same Project. In this sense, the author states that the meaning of the aforementioned article should be clarified in order to determine the law of the international contract and the recognition of the consequences of its application. Therefore, it is suggested that the parties be allowed to opt for a foreign law that always has an objective relationship with the contractual relationship. In short, a legal framework is proposed that is consistent in its provisions, permissive and limiting, that balances individual freedom in the international field with the protection of national imperative norms. It is very important to emphasize that Peruvian imperative norms are protected by not applying the foreign law or recognizing the consequences of their application if they violate the Peruvian public order.